Faktor-Faktor Yang Mempengaruhi Niat Adopsi Mobile Banking Bank Syariah Indonesia di Kabupaten Kudus - Nur, Fatikha Rizqya; Hadi, Nor; Dewi, Adelina Citra (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
This article describes the results of testing the theory of planned behavior (TPB) which specifically examines the factors influencing intention of adoption of mobile banking. The research was conducted on customers of the Kudus branch of Bank Syari'ah Indonesia (BSI) in 2023. The research data was primary using a survey data collection technique, namely distributing questionnaires to BSI customers using mobile banking. The population is all customers of the BSI holy branch, with a total sample of 168 respondents. The sampling technique used is incident sampling. To analyze the data, the Structure of Equation Model (SEM) is used. The results showed that the hypothesis about the effect of perceived usefulness, perceived ease of use, and spiritual motivation proved to have a significant effect on the intention to adopt mobile banking. While social influence has no significant effect on the intention of adopting mobile banking. Meanwhile, the hypothesis that tests the effect of perceived usefulness, perceived ease of use, spiritual motivation, and adoption intention on the actual use of mobile banking is proven to have a significant effect. While the hypothesis about social influence has no effect on the actual use of mobile banking.